Reference value of quantitative. examination of urine sediment using Shih-Yung (S-Y) system - Riadi Wirawan Riadi Wirawan (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2004)
Background: Conventional urine sediment examination was reported semiquantitatively, Shih-Yung system was quantitative and standaridizeci method.Objective: To evaluate urine sediment examination using Shih-Yung systems and to determine the reference value.Material and methods: Normal and pathologic urine from patients who have renal and urinary tract disorders, control material for urine microscopic examination Kova-TrolTm I and also urine from 120 healthy men and 120 healthy women.Results: Within run precision using normal urine, pathologic urine, and Kova-TrolTm I yielded a different coefficient of variation (CV) for small and large amount urine sediment component. Laboratory agreement between two observer using Kappa test were >80% for each urine sediment component. Reference values of urine sediment component were as follows: red cells 0-2/4, white cells 0-4/4, hyalin cast 0/ pL, epithelial cell for men 0-1/4 and epithelial cell for women 0-9/4.Conclusion: a relative big CV for small amount urine sediment component and vice versa. Reference values of urine sediment component were as follows: red cells 0-2/4, white cells 0-4/4, hyalin cast 0/epithelial cell for men 0-1/4 and epithelial cell for women 0-9/4. Shih-Yung system yielded a good laboratory agreement between two observers using Kappa test.Key words: urinalysis - urine sediment - quantitative examination - S-Y system - normal value